“Ethics”, “Morality” and Augustinian Liberum Arbitrium - Eksen, Kerem (Problemos, 2009)
The present paper aims at a reconsideration of the terminological distinction – postulated by eminent contemporary thinkers such as Alasdair MacIntyre and Bernard Williams – between “ethics” and “morality”. Although this distinction has not been settled as a standard*, there is no doubt that it incited fruitful debates relating to the contemporary issues of moral philosophy as well as the history of ethics. Julia Annas, to take one considerable example, presented a full-fledged criticism of the distinction and touched upon crucial questions**. In the following pages, we shall take the general argument of Annas as our starting-point, and reevaluate it with reference to a particular moment in the history of ideas, in order to shed light on the proposed distinction. To this end, we shall focus on the philosophy of Augustine, more precisely on his De Libero Arbitrio (On Free Choice), with the aim of comprehending the novelty of his contribution to the history of ethics. We shall show how Augustine, through his original usage of the concept of voluntas (will), reorganized the sphere of ethics and redefined the relationship between happiness (beatitudo) and right action. We will thereby illustrate that the ethics / morality distinction is highly illuminating for getting the real sense of this process of redefinition and reorganization, as well as the broader transformation that it triggered in the way human action will be problematized by later generations.